Pengaruh Ukuran Partikel dan Feed Rate Pasir pada Sistem Sanding Kereta Api terhadap Kecepatan Putaran dan Kekasaran Permukaan Roda dan Rel - Paryanto, Paryanto (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2020)
Sanding is a method where a certain amount of sand is sprayed between the wheels and rails during emergency braking or other operations that require high coefficient of friction. However, an inappropriate sanding method can accelerate the wear and damage the surface of the wheels and rail. Therefore, this study aims to determine the most efficient parameters of the sand size and its feed rate for increasing the friction coefficient between the wheels and rails. The experimental is conducted using ST 60 steel for the wheel and ST 90 steel as rail test specimen. The experiments are done by rotating the wheel specimen on the rail specimen with a constant speed at 400 rpm. After that, water is dropped to the surface of the wheels and rails specimens at the flow rate 2 ml/min to create a wet surface condition. In the experiments set up, there are three sand variations of grain size, i.e. mesh 80-200, mesh 30-50, and mesh 20-30 with sanding rate 5 gram/min, 7 gram/min, and 10 gram/min. Based on the experimental results, it was found that the larger the sand grain size and feed rate, the slip ratio between the wheel and rail will decrease but the surface roughness of the wheel and rail will also increase. The optimal sand size for reducing the slip ratio between wheels and rails is 20-30 mesh sand (with 0.595-0.841 mm grain size) and at 10 gram/min feed rate. At this condition, the slip ratio between the wheel and rail is reduced to 1.05% with surface roughness value (Ra) of wheel 4.84 Î¼m and 3.87 Î¼m for rail specimen.